Impact of an infectious disease specialist-led antimicrobial stewardship program and consultations during multiple antimicrobial shortages: A bayesian structural time-series analysis - Naoya Itoh; Nobumasa Okumura; Nana Akazawa-Kai; Chiharu Wachino; Shunsuke Kuriki; Takanori Kawabata (PLoS ONE, 2026)
Since antimicrobial shortages are becoming common owing to manufacturing issues and sudden demand, individualized antimicrobial optimization by infectious disease specialists is essential. We evaluated the effects of a 12-month antimicrobial stewardship program at a university-affiliated hospital in Japan during antimicrobial shortages. In this single-center retrospective observational study, from April 1, 2023, to March 31, 2025, we compared the pre-intervention (antimicrobial stewardship program without infectious disease specialists) and post-intervention (antimicrobial stewardship program with infectious disease specialists and formal consultation service) periods. The evaluated outcomes included antimicrobial use, microbiological indicators (number of culture specimens submitted and hospital-acquired resistant organisms), patient outcomes (in-hospital mortality and length of hospital stay), and antimicrobial costs. A Bayesian structural time-series analysis adjusted for seasonality was used to assess intervention effects. In total, 24,601 inpatients were included (11,782 before intervention and 12,819 after). Shortages affected nine intravenous and two oral antibiotics. The antimicrobial stewardship program team provided 1110 feedback instances (acceptance rate, 74.1%) and conducted 172 infectious disease consultations in the post-intervention period. Carbapenem use, antipseudomonal agent use, incidence of carbapenem-resistant Pseudomonas aeruginosa , and the cost of carbapenems per patient-day significantly decreased. Narrow-spectrum antibiotic use, anti-methicillin-resistant Staphylococcus aureus agent use, all intravenous antimicrobial use, total intravenous and oral antimicrobials, and the number of inpatient specimens were significantly increased. All antimicrobial costs, in-hospital mortality, and length of hospital stay remained unchanged. Antimicrobial stewardship program supported by infectious disease specialists/consultants significantly reduced carbapenem and antipseudomonal agent use without negatively affecting patient outcomes. These findings highlight infectious disease specialists’ critical role in supporting effective antimicrobial stewardship programs, particularly during limited antimicrobial supply and increased clinical complexity.